Green Sourcing: Supplier Assessment and Selection Practices across Industries - Emmanuel D. Adamides; Yannis Mouzakitis (Logistics, 2024)
Background: Over the last years, the assessment and selection of suppliers, based on the environmental performance of their products/services and their operations, has reached paramount importance and attracted the interest of many researchers and practitioners. Based on the prevailing perspective of supplier selection as a purely decision-making problem, this interest has been channeled towards the development of decision-support methods and tools. Other broader issues, such as whether there are converging or diverging green supplier evaluation and selection organizational processes across industries has not been addressed. Methods: Here, for the first time, we address this question by adopting a systems perspective and by considering green supplier evaluation and selection as an organizational sub-process of the broader sourcing process. We use activity theory to represent green supplier evaluation and selection as two interconnected activities, each comprising a set of organizational practices. Based on this representation, we developed a research instrument to carry out empirical research in a sample of 80 companies from five industries (pharmaceuticals, food processing, aquaculture, construction materials, waste management and recycling) in Greece. Results: The results of the survey suggest that green supplier evaluation and selection practices do not fully converge, but there are differences across industries. Conclusions: The cultural and historical context of industries influences the adoption of specific environmental supplier evaluation and selection practices.